IAS/IFRS in Belgium: Quantitative Analysis of the Impact on the Tax Burden of Companies - Jacqueline Haverals (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
The adoption of IAS/IFRS in the European Union is part of the European Commission?s global tax policy whose aim is to establish a coordinated corporate tax base. The paper examines the impact of an IAS/IFRS- based tax accounting on the effective tax burden of Belgian companies for eleven different sectors. The use of IAS/IFRS as a starting point for tax purposes affects differently each sector, depending on its accounting and financial characteristics. Some sectors like construction and automotive vehicles see much larger increases in effective tax burdens than others but the impact remains in general relatively important.
Keywords: H25; H21; 330; IAS/IFRS; tax law; tax burden; Unternehmensbesteuerung; Steuerbilanz; International Financial Reporting Standards; EU-Bilanzrecht; Steuerbemessung; Steuerbelastung; Branche; Belgien